Research on sand resistance performance of comprehensive protection facilities for desert hinterland highways under strong wind environment - Wenhua Yin; Xu Wang; Yongxiang Wu; Fang Wang (Archives of Civil Engineering, 2022)
Based on the test and observation of the desert hinterland wind field, combined with the numerical simulation of Fluent wind-sand two-phase flow, the sand resistance performances of comprehensive protection in the desert hinterland under strong wind environment are researched. The transient wind speed and wind direction around the comprehensive protection facility are measured by two 3D ultrasonic anemometers on the highway in the desert hinterland, and the initial wind speed of the sand flow is provided for the numerical simulation boundary. The sedimentary sand particles around the comprehensive protection facility are collected for particle size analysis, and the particle size distributions of sedimentary sand particles at different locations are obtained. Numerical models of high vertical sand barriers, grass checkered sand barriers and roadbeds are established by Fluent, the wind-sand flow structures around the comprehensive protection facilities and desert hinterland highway under the strong wind environment are obtained, and the influence laws of the comprehensive protection facilities on the movement of wind-sand flow and sand deposition characteristics are obtained. The study found that the comprehensive protection facilities disturbed the wind and sand flow, and there are significant airflow partitions around the comprehensive protection facilities. The wind speed decreases rapidly after the wind-sand flows through the high vertical sand barrier; the wind-sand flow rises at the end of the high vertical sand barrier. When the wind-sand flow moves around the grass checkered sand barrier, the wind speed has dropped to the range of 0–3 m/s, and the wind speed near the ground by the grass checkered sand barrier is further reduced. Due to the existence of the concave surface of the grass grid, there are small vortices inside the grass grid sand barrier. Large sand particles are mainly deposited on the windward side and inside of high vertical sand barriers. The grass checkered sand barrier forms a stable concave surface to generate backflow, which can ensure that the sand surface does not sand itself in a strong wind environment, and can also make a small amount of sand carried in the airflow accumulate around the groove of the grass checkered sand barrier. The numerical simulation results are consistent with the measured results, and the comprehensive protection measures have achieved good sand control effects.